2007
DOI: 10.1007/s11136-007-9202-8
|View full text |Cite
|
Sign up to set email alerts
|

Health related quality of life in different states of breast cancer

Abstract: This study shows that breast cancer is associated with a reduction in HRQoL. This effect is most pronounced for patients with metastatic disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

13
153
3
7

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 197 publications
(181 citation statements)
references
References 32 publications
(32 reference statements)
13
153
3
7
Order By: Relevance
“…The criteria for the values that they selected in their analysis were that they would ideally be based on EQ-5D scores, would ideally have been derived from UK patients and these patients would ideally reflect the younger age range of patients in the TARGIT-A trial. The values that they selected, from studies by Turnbull et al 87 and Lidgren et al, 88 were as follows:…”
Section: Utilities and Quality-adjusted Life-yearsmentioning
confidence: 99%
“…The criteria for the values that they selected in their analysis were that they would ideally be based on EQ-5D scores, would ideally have been derived from UK patients and these patients would ideally reflect the younger age range of patients in the TARGIT-A trial. The values that they selected, from studies by Turnbull et al 87 and Lidgren et al, 88 were as follows:…”
Section: Utilities and Quality-adjusted Life-yearsmentioning
confidence: 99%
“…132,134 All nine included studies defined the study question and explained the treatment strategies. Across the studies, the study designs as well as the methods of recruiting participants were clearly outlined.…”
Section: Critical Appraisal Of the Included Studiesmentioning
confidence: 99%
“…Full data extraction of all the included studies is shown in Appendix 8. The nine studies provided data for five out of the seven health states potentially relevant for the independent model: disease free after WLE (one study), 126 WLE + WB-EBRT (three studies), [127][128][129] disease free after local recurrence (one study), 132 mastectomy and reconstruction (two studies), 130,131 and distant recurrence/ metastatic breast cancer (three studies). 132,133,134 No EQ-5D data were identified for the health states WLE + INTRABEAM or WLE + INTRABEAM + WB-EBRT.…”
mentioning
confidence: 99%
See 2 more Smart Citations